(untitled) (KULT_online, 2015)
“News narrates stories” – this is the central thesis of Christoph Bietz’ monograph. By bridging the basic concepts of News Theory and Narratology, he shows that the news has no choice other than to narrate. Those narratives are independent from categories such as facticity and fiction, and they might even contribute to the claim of authenticity within the News itself. In detailed analyses Bietz develops a narratology of telemedial news and fundamentally challenges the conventional approaches of News Theory with its claim of objectivity.